(3MdHI GdcejJs - (3GdfhGLj, TeS GdOjf, eMeO Hf MSf Hf Ydj Hf YKeGf, J (B859 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3abO SCdfj ef CeQg eWGY heNGdaJg dG JSJWGY Cf GLeY dg ef ebGWY GdTQH fHPI QajYI GdHRI QbjbI GdMGTjI , hCbJWa dg ef MOGFb GdCOH RgQI bWhagG OGfjI djfRg WQag aj LfGJ ef fNjd hCYfGH (B...s
(3BNQgG (B:s
..(3hMcj Gf GdeJfHj cGf jCHi TQH GdNeQ hjcQgg aCdReg Sja GdOhdI djdI GdTQGH (B.. (3Ke fOe dhbJg abGe hGfUQa hHbj CjGeG dG jMVQ eLdS Sja GdOhdI aCcKQ ef WdHg hCMVQg hCeQ HGdTQGH aGeJfY hCbSe Cfg dG jTQH NeQG hCfTO jbhd (B... (3JeJs
(3JHUQI GdYfhGf (B:s
(3aj GdCOH hGdfhGOQ GdeJYdbI HGdNeQjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/88s
(3cTa GdXfhf (B1/687s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs